2016
DOI: 10.1177/0271678x16659496
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous incidence and propagation of spreading depolarizations

Abstract: Spreading depolarizations are implicated in a diverse set of neurologic diseases. They are unusual forms of nervous system activity in that they propagate very slowly and approximately concentrically, apparently not respecting the anatomic, synaptic, functional, or vascular architecture of the brain. However, there is evidence that spreading depolarizations are not truly concentric, isotropic, or homogeneous, either in space or in time. Here we present evidence from KCl-induced spreading depolarizations, in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 53 publications
(101 reference statements)
8
47
0
Order By: Relevance
“…Another read-out to be taken as an indicator for the susceptibility of the nervous tissue to SD is the distance covered by SD before coming to a halt. Indeed, some SD events are gradually extinguished over their course of propagation, rather than traversing the entire cortical surface, as demonstrated by multimodal experimental imaging studies (Bere et al, 2014;Kaufmann et al, 2017;Menyhart et al, 2017a). Even though not documented so far, we observed that in old (18 months old) rats, experimentally triggered SDs are more likely to terminate after having propagated only a few millimeters away from the site of elicitation than in young (2 months old) rats.…”
Section: Sd Triggered Experimentallymentioning
confidence: 53%
“…Another read-out to be taken as an indicator for the susceptibility of the nervous tissue to SD is the distance covered by SD before coming to a halt. Indeed, some SD events are gradually extinguished over their course of propagation, rather than traversing the entire cortical surface, as demonstrated by multimodal experimental imaging studies (Bere et al, 2014;Kaufmann et al, 2017;Menyhart et al, 2017a). Even though not documented so far, we observed that in old (18 months old) rats, experimentally triggered SDs are more likely to terminate after having propagated only a few millimeters away from the site of elicitation than in young (2 months old) rats.…”
Section: Sd Triggered Experimentallymentioning
confidence: 53%
“…22 Our findings are in agreement with easier induction and faster propagation of SD 7,29 and higher frequency of recurrent SDs 23 in the superficial cortical layers, and with preferential propagation of SD through the superficial layers in slices of the neocortex in vitro. 23,[30][31][32] In addition, we found that about half of SDs generated in superficial layers were arrested at the border between superficial and deep layers, whereas fully propagating SDs often slowed down at a depth of ~1000 μm (example shown in Figure 4A). This is in keeping with a kind of "barrier" for vertical SD propagation and segregation of SDs in the superficial and deep cortical layers previously reported for recurrent SDs evoked by continuous remote high potassium application.…”
Section: Discussionmentioning
confidence: 81%
“…A titanium omega bar was cemented to the interparietal bone, and exposed skull and scalp margins were sealed with cement. In a subset of experiments, the skull was thinned over the barrel cortex rather than removed (3 mm x 3 mm square) (Figures S1 and S2) (Kaufmann et al, 2017).…”
Section: Surgery For Awake Imagingmentioning
confidence: 99%